Chemical homogeneity and particle size distribution of dairy cow TMR along the feeding alley with different mixing times (International Journal of Health, Animal Science and Food Safety, 2018)
Following the concepts of precision feeding, the right components balance (Sova et al., 2014) and the correct particle size distribution (PSD, Khan et al., 2014) of total mixed ration (TMR) are essential for a complete homogeneity of the diet and are strongly influenced by adopted mixing time (MT, Humer et al., 2018, Schingoethe et al.,2017). The aim of the trial was to determine the influence of two MTs (MT1≤7min and MT2>7min) on the chemical homogeneity and PSD along the feeding alley. Diets were performed with a horizontal cutter-mixer wagon (Gulliver 4016, Sgariboldi), and TMR samples were collected from the beginning, middle and end of the feeding alley after discharge. Triplicate samples of the diet were collected for chemical composition analyses (moisture, CP, Ash, EE, NDF and ADF) and PSD evaluation (Heinrichs and Kononoff, 2002) over two months (two sampling/week). Statistical analysis was performed by a PROC MIXED for repeated measurements of SAS. MT1 evidenced a non-uniform distribution of moisture content along the feeding alley (P=0.05): lower moisture was found at the end than at the beginning and in the middle (47.55 vs 51.13 and 51.00%, respectively; P
Keywords: Total mixed ration; Dairy cows; Mixing time; Mixing wagon; Particle size distribution